TINJAUAN YURIDIS SENGKETA KEPEMILIKAN MEREK SUPREME - Ananda Putri Safira; Elfrida Ratnawati Gultom; Putri Safira, Ananda (Reformasi Hukum Trisakti, 2023)
The Law No. 20 of 2016 Concerning Marks and Geographical Indications, which addresses brands and geographical indications, regulates the strong relationship between marks and unfair competition. The formulation of the problem in this study is how to resolve disputes over ownership of the SUPREME brand according to Trademark Law and whether or not the Judge's decision in the dispute over ownership of the SUPREME brand, Central Jakarta Commercial Court Number 10/Pdt.Sus-Merek/2021/PN.Niaga.Jkt.Pst, is appropriate or not according to Trademark Law. Normative legislation underlies this research approach, which has the nature of analytical descriptive research, the object of research is disputes over ownership of the SUPREME brand, collecting data through literature studies, analyzing data using qualitative analysis methods, and drawing conclusions using deductive methods. The results of the research and discussion show that it is not in accordance with the existing provisions, the judge does not accept the plaintiff's request because the lawsuit has expired. The conclusion is that the owner of the registered mark or the licensee can file a lawsuit against another party with the principal similarities or in its entirety, the Judge's decision can be said to be erroneous and not in accordance with the applicable law.